Haem Biology in Metazoan Parasites – 'The Bright Side of Haem'. Issue 3 (March 2019) - Perner, Jan; Gasser, Robin B.; Oliveira, Pedro L.; Kopáček, Petr
Abstract : Traditionally, host haem has been recognized as a cytotoxic molecule that parasites need to eliminate or detoxify in order to survive. However, recent evidence indicates that some lineages of parasites have lost genes that encode enzymes involved specifically in endogenous haem biosynthesis. Such lineages thus need to acquire and utilize haem originating from their host animal, making it an indispensable molecule for their survival and reproduction. In multicellular parasites, host haem needs to be systemically distributed throughout their bodies to meet the haem demands in all cell and tissue types. Host haem also gets deposited in parasite eggs, enabling embryogenesis and reproduction. Clearly, a better understanding of haem biology in multicellular parasites should elucidate organismal adaptations to obligatory blood-feeding. Highlights: Ticks and nematodes do not code for haem biosynthetic and degrading enzymes, likely operating independent haem and iron acquisition/distribution networks. The uptake of exogenous haem brings a selective advantage in a haem-rich environment, even in the presence of functional haem biosynthesis. The unavailability of host haem is often manifested during embryogenesis, and the formation of progeny is conditioned by deposits of host haem.